Paradox of Legal Protection for Kid Influencers and Artists in Indonesia: Comparative Study of Us and France - Alfiyah, Andi Besse; Wiranti, Wiranti; Abrar, Ahmad Nugraha; Annisa, Arini Nur; Parawansa, Syarif Saddam Rivanie; Iskandar, Ismail (International Journal of Law Reconstruction, 2025)
Every country has to fulfill legal protection for children. In this digital era, social media have positive and negative impacts on children. The number of children using social media is the third highest, namely aged 5-12 years. The economic exploitation of children reaches 431 cases. This study aims to investigate these 3 cases based on the regulation and comparison with other countries. This qualitative research used Normative Jurisprudence, Case Study, and Statue Approaches. Normative Jurisprudence referred to the Child Protection Law and the Employment Law. The case study involved 3 cases and the status approach compared regulations between the United States and France.  This study revealed the urgency of the protection of child labor in the entertainment industry, namely kid influencers and artists who experience legal uncertainty due to the ambiguity and inequality of norms. Elements of the Criminal Act of Child Exploitation were fulfilled with the constraints in the explanation of the "Types of Economic Exploitation Acts" for child influencers or artists. Changes to related laws or legal reform through the Child Labor Law Draft need to consider the United States and France, which have succeeded in providing such protection.